Pencegahan Penyakit Pada Ternak Ayam Kampung Melalui Bimbingan Teknis Manajemen Sanitasi dan Biosecurity di Kecamatan Abeli - Libriani, Restu; Nafiu, La Ode; Saili, Takdir; Abadi, Musram; Sulfitrana, Andini; Salido, Wa Laili; Isnaeni, Purnaning Dhian (Jurnal Pengabdian Masyarakat Ilmu Terapan (JPMIT), 2020)
Biosecurity is an integral concept that influences the success of livestock production systems, especially in reducing the risks and consequences of infectious and non-communicable diseases. The problem faced by breeders in Abeli District is the lack of knowledge of breeders about maintenance systems that meet the eligibility standards of commercial native chicken farms, handling biosecurity, sanitation and animal health against diseases that are not yet optimal, so that native village chickens are often exposed to various diseases. Through the Thematic KKN FPt UHO program, efforts should be made to improve the knowledge and skills of farmers about bisecurity management that meets the standards for commercial village chicken farms. This service is carried out for one month, starting from June 13, 2020 to July 13, 2020, Abeli District, Kendari City. This community service activity was carried out by involving Thematic KKN FPt UHO participants. The program is carried out in the form of Technical Guidance and Counseling, namely (1) Bimtek and virtual / online counseling; and (2) Bimtek and counseling using face-to-face methods both individually and more and still pay attention to the Covid-19 prevention protocol. The material for this service program is handling biosecurity, sanitation and animal health. The results that have been achieved in the Thematic KKN FPt UHO program are improving the knowledge and skills of breeders in biosecurity management procedures which include three main activities namely isolation, traffic control and sanitation as an effort to prevent transmission of disease in native chicken farms